(untitled) (Journal of Medical & Health Sciences Review, 2025)
Arteriovenous fistula (AVF) stenosis is one of the most frequent complications among patients receiving hemodialysis, leading to inadequate blood flow, impaired dialysis adequacy, repeated interventions, and AVF management. This study evaluated the effectiveness of a structured AVF stenosis prevention program designed to improve vascular access outcomes through exercise, nutrition, and patient education. A quasi-experimental design was used, and 62 patients undergoing hemodialysis at a tertiary care hospital were purposively selected. The intervention comprised a phosphorus-restricted diet, upper extremity strengthening with a hand gripper, postoperative AVF care instructions, motivational text messages, and ongoing counseling. Data were collected on upper limb muscle strength, AVF blood flow, physiological markers of vascular calcification (serum calcium and phosphorus), and self-care behavior before and after the intervention. Results indicated significant improvements in muscle power, blood flow rate, and physiological indices, along with enhanced patient self-care behaviors. The findings suggest that incorporating exercise and dietary counseling into routine hemodialysis can prevent stenosis, prolong AVF patency, and reduce complications. This study underscores the importance of a multidisciplinary approach in empowering patients with self-management strategies to improve quality of life and ensure sustainable hemodialysis outcomes.